Tháng Ba 1, 2024

Giá trị của biểu thức \(A = \left( {{y^2} + 2} \right)\left( {y – 4} \right) – \left( {2{y^2} + 1} \right)\left( {\frac{1}{2}y – 2} \right)\) tại \(y = – \frac{2}{3}\) là:

Giá trị của biểu thức \(A = \left( {{y^2} + 2} \right)\left( {y – 4} \right) – \left( {2{y^2} + 1} \right)\left( {\frac{1}{2}y – 2} \right)\) tại \(y = – \frac{2}{3}\) là:

A. \( – 6\)

B. \( – 7\)

C. \( – 5\)

D. \( – 9\)

Hướng dẫn Chọn đáp án là: B

Lời giải chi tiết:

Hướng dẫn giải chi tiết

\(A = \left( {{y^2} + 2} \right)\left( {y – 4} \right) – \left( {2{y^2} + 1} \right)\left( {\frac{1}{2}y – 2} \right) = {y^2}.y – 4.{y^2} + 2.y – 2.4 – 2{y^2}.\frac{1}{2}y + 2.2{y^2} – 1.\frac{1}{2}y + 1.2 = \frac{3}{2}y – 6\)

Tại \(y=-\frac{2}{3}\) ta có: \(A=\frac{3}{2}.\left( -\frac{2}{3} \right)-6=-7\)

Chọn B